Studies on the behaviour of Pseudomonas fluorescens biofilms after ortho-phthalaldehyde treatment - Simões, M. (2003)
A relatively novel biocide, ortho-phthalaldehyde (OPA), was tested to control biofilms formed by Pseudomonas fluorescens on stainless steel surfaces. The toxic action of OPA was assessed in terms of inactivation and removal of the biofilm by means of, respectively, the determination of the respiratory activity and the variation in the dry weight of the biofilms. For comparison, the activity of OPA against suspended bacteria was also evaluated. The results showed that higher concentrations of OPA and longer exposure times are needed to inactivate P. fluorescens biofilms than planktonic populations, thus denoting that sessile bacteria have a reduced susceptibility to OPA. This appears to be associated with the reaction with the proteins of the matrix, as demonstrated by the reduction of the antimicrobial action of OPA in the presence of a protein (bovine serum albumin). The application of OPA appeared to cause little effect in the removal of biofilms from the metal slides since the mass of biofilm that remained on the surfaces, after biocide treatment, was within the same range as those observed in the control tests. These results suggest that, with OPA application, biofilms can be inactivated but stay attached to the surfaces, decreasing thereby the success of the chemical treatment.